2018
DOI: 10.1055/s-0038-1624572
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Skull Base Approaches in Pediatric Skull Base Surgery

Abstract: Lateral skull base pathology is rare in children. Awareness of the potential for lateral skull base lesions in children is imperative for timely identification and appropriate management. Some of the common presentations and pathologies shall be presented, as well as a variety of approaches that may be utilized to access the lateral skull base in the pediatric patient. Although the lateral skull base approaches utilized in adults may also be considered for management of pediatric lesions, some special consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…23 For lateral skull base (transpetrous) approaches, considerations include the possible lack of mastoid pneumatization in children and a lower rate of cerebrospinal fluid leakage. 24 One study found that the degree of sphenoid pneumatization did not affect outcome in children who underwent endoscopic endonasal resection of craniopharyngioma, 25 although it remains an important age-related consideration and may be a critical factor in approach selection. More generally, hemostasis is of particular importance in children because they have smaller circulating blood volume, and relatively immature prominent bony facial features may affect the accuracy of neuronavigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 For lateral skull base (transpetrous) approaches, considerations include the possible lack of mastoid pneumatization in children and a lower rate of cerebrospinal fluid leakage. 24 One study found that the degree of sphenoid pneumatization did not affect outcome in children who underwent endoscopic endonasal resection of craniopharyngioma, 25 although it remains an important age-related consideration and may be a critical factor in approach selection. More generally, hemostasis is of particular importance in children because they have smaller circulating blood volume, and relatively immature prominent bony facial features may affect the accuracy of neuronavigation.…”
Section: Discussionmentioning
confidence: 99%
“… 23 For lateral skull base (transpetrous) approaches, considerations include the possible lack of mastoid pneumatization in children and a lower rate of cerebrospinal fluid leakage. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17] However, few studies are Pattern of malignant head and neck tumors among children in a Nigerian Teaching Hospital Edetanlen Benlance E et al reported in sub-Saharan Africa. 18,19,20 Hence, this present study evaluated the pattern of malignant head and neck tumors among children in the south-south geopolitical region of Nigeria.…”
Section: Introductionmentioning
confidence: 99%